2020
DOI: 10.7759/cureus.6735
|View full text |Cite
|
Sign up to set email alerts
|

Hemi-hamate Arthroplasty in Chronic Fracture-dislocation of Proximal Interphalangeal Joint of Fingers: A Report of Two Cases

Abstract: Dorsal dislocations of proximal interphalangeal joint with palmar lip fractures base of middle phalanx of fingers are rare, complex, and often a challenging injury to the treating hand surgeons especially in those chronic cases. Hemi-hamate arthroplasty is the preferred surgical option in treating chronic dorsal fracture-dislocations of the proximal interphalangeal joint. We report two cases with a chronic injury that have been treated with hemi-hamate arthroplasty. Range of motion, pinch and grip strengths, Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Hemihamate arthroplasty is a treatment option for unstable chronic dorsal fracture-dislocations of the PIPJ. The literature reports a 63 to 90 degrees arc of motion in patients who have undergone a HHA 8–10,13,14,17–19 . The majority of these studies (4 of 7) report between 63 and 69 degrees arc of motion, similar to the average postoperative arc of motion (63 degrees) reported in our series (Table 4).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Hemihamate arthroplasty is a treatment option for unstable chronic dorsal fracture-dislocations of the PIPJ. The literature reports a 63 to 90 degrees arc of motion in patients who have undergone a HHA 8–10,13,14,17–19 . The majority of these studies (4 of 7) report between 63 and 69 degrees arc of motion, similar to the average postoperative arc of motion (63 degrees) reported in our series (Table 4).…”
Section: Discussionsupporting
confidence: 84%
“…The literature reports a 63 to 90 degrees arc of motion in patients who have undergone a HHA. [8][9][10]13,14,[17][18][19] The majority of these studies (4 of 7) report between 63 and 69 degrees arc of motion, similar to the average postoperative arc of motion (63 degrees) reported in our series (Table 4). Two systematic reviews reported an average postoperative PIPJ motion of 77 degrees (Frueh et al 4 ) and 74 degrees (Faulkner et al 11 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Open reduction is recommended and fractured fragments can be fixed with 1.5 or 2.0 mm screws or a min fragment buttress plate over a volar plate area to reduce comminuted fragments [ 12 ]. When the fractured fragments with the attached volar plate are not amenable for osteosynthesis, reconstruction of the volar plate by VPA [ 3 ] or hook of the hamate graft [ 11 , 13 , 14 ] reconstruction of the base of middle phalanx is the standard of care. Tenodesis with FDS and arthrodesis of PIP joint were reported by few authors in the literature [ 15 ].…”
Section: Discussionmentioning
confidence: 99%